Concentration dependence of Cr for alleviating environmental embrittlement in Fe30Ni20Mn35Al15. (January 2015) - Meng, Fanling; Bauer, Samuel F.; Liao, Yifeng; Baker, Ian
Abstract: Previously, it has been shown that Fe30 Ni20 Mn35 Al15, which consists of alternating submicron B2 and f.c.c. lamellae, exhibits a room temperature yield strength of 770 MPa and an elongation of ∼10% at a strain rate of 3 × 10 −3  s −1 in air, but at the slower strain rate of 3 × 10 −6  s −1 the alloy exhibits an elongation <1%[1] . An addition of 6 at% Cr has been proven to not only solve this environmental problem, but also to increase the elongation to 15–18% irrespective of strain rate[2] . Since we do not know whether Cr additions less than 6 at% can suppress this environmental embrittlement, in this paper we examined the room temperature mechanical properties of several alloys based on Fe30 Ni20 Mn35 Al15 with Cr additions ≤6 at%. We show that additions as low as 0.5 at% Cr alleviate the environmental embrittlement and that additions of ≥2 at% completely suppress the embrittlement with little change in microstructure. X-ray photoelectron spectroscopy examination suggested that the suppression is mostly due to the formation of protective oxide scales on the surface that provide rapid passivation. The lower yield strength when Cr is present may also contribute to the improved ductility, possibly by easing dislocation cross-slip in the deforming f.c.c. phase where most of the Cr resides. Graphical abstract: